Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed